Physiotherapeutic methods in the treatment of heel spurs and inflammation of plantar fasciitis - a review of the literature - Uczciwek, Mariola Monika (Journal of Education, Health and Sport, 2017)
For aim of this paper and analysis of the treatment methods in question articles from Pumbed basis were used. Pumbed basis, which works under the auspices of US National Library of Medicine and National Institute of Health, helped to analyze the treatment methods for chronic condition of heel spur and plantar fascia. The analytical process was based on bibliographical descript. Results of 1204 numbers were summarized because of specialist criterion. Heel spurs are bony growths growing out of the plantar fascia and other soft tissues lining nearby which conduct to the plantar fascia ignition. The occurrence of these is connected with burdensome feeling of pain that can be felt when making first steps after getting up in the morning. It is a serious condition that applies to more and more people. Being overweight, training sports straining feet are the reasons contributing to this condition. Yet, it is not a general rule for the risk group. Treating methods in this sphere give many opportunities for physical therapist and doctors. The best sustainable method is physical therapy supported by medical aids. However, not every case gives intended results. If the sustainable methods are not enough, the surgical treatment should be introduced. There is no doubt that any method of treatment is individually reclaimed by every patient.